2021
DOI: 10.5114/fn.2021.109434
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical aspirin resistance in acute stroke patients and its association with clinical factors: a prospective pilot study

Abstract: Introduction: Aspirin is still widely used in treatment and prevention of cardiovascular diseases. To predict which patients cannot benefit from aspirin due to aspirin resistance remains a great clinical challenge. Material and methods: Fifty one acute stroke/transient ischemic attack (TIA) patients (ASG) with a history of regular aspirin intake for the previous 7 days or more were included to the study within 24 hours of symptoms onset. Twenty nine patients admitted to our department for other reasons were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Aspirin has an irreversible inhibitory effect on platelet aggregation through acetylated platelet cyclooxygenase, while clopidogrel, as an adenosine diphosphate receptor inhibitor, inhibits platelet aggregation. For patients who took antiplatelet agents regularly and still had AIS, the possible cause was aspirin resistance [ 54 ] or clopidogrel resistance [ 55 ], which may explain that the study treatment can only reduce the risk of recurrent stroke significantly in patients of the subgroup of non-antiplatelet, but not in patients of the subgroup of prior-antiplatelet.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin has an irreversible inhibitory effect on platelet aggregation through acetylated platelet cyclooxygenase, while clopidogrel, as an adenosine diphosphate receptor inhibitor, inhibits platelet aggregation. For patients who took antiplatelet agents regularly and still had AIS, the possible cause was aspirin resistance [ 54 ] or clopidogrel resistance [ 55 ], which may explain that the study treatment can only reduce the risk of recurrent stroke significantly in patients of the subgroup of non-antiplatelet, but not in patients of the subgroup of prior-antiplatelet.…”
Section: Discussionmentioning
confidence: 99%
“…4 In clinical practice, some patients still suffer from malignant cardio-cerebral vascular incidents after regular administration of aspirin. 5,6 Some studies found that factors such as age and underlying disease are associated with the potency of aspirin. In contrast, bleeding events occurred in some patients during medication due to the strong antiplatelet effect.…”
Section: What Is Known and Objectivementioning
confidence: 99%